Augmented reality (AR)-based experimental learning: A solution to overcome boredom with worksheet usage in generation alpha (Gen-A) early childhood - Nuha Rahmadiah Khoirunnisa; Muslam Muslam (Journal of Early Childhood Care and Education, 2025)
Generation Alpha (Gen-A), who have grown up in the digital era, are more interested in interactive and visual learning. However, traditional methods such as worksheets are considered monotonous, reducing motivation and engagement in learning. This study aims to implement Augmented Reality (AR) based Experimental Learning as an innovative solution to overcome the boredom of Gen-A children with conventional worksheets in Early Childhood Education (ECE). The research gap lies in the lack of exploration of AR in ECE, particularly in Indonesia, as well as the limited studies on the learning needs of early childhood. This research uses a descriptive qualitative method with observation, interviews, and document analysis at RA Nurul Ulum. The results show that conventional worksheets are boring and decrease children's learning motivation. These findings emphasize the importance of AR-based and experiential learning innovations that are adaptive to the characteristics of Gen-A, creating a more engaging and effective learning environment.